Participation of Family Planning Acceptors with The “Bobodoran” Culture Approach in The Community of Sumulagung Village Cikunir Tasikmalaya 20 - Chanty Yunie Hartiningrum; Annisa Rahmidini (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
One strategy to lower Maternal Mortality Rate (MMR), Infant Mortality Rate, as well as the total fertility rate (TFR), is with family planning, was by family planning, the main target is an unmet need and mother after childbirth. This was done to the increase in maternal health, especially in reproduction. Based on the results of a survey that applied Sumulagung hamlet Kabupaten Tasikmalaya, these charges in the future the results of that there were still 12,5 % woman are in their reproductive age (WUS) who have not yet use contraceptive tools, wus have used a contraceptive device itself has yet to does not reflect the objectives in family planning and how old it is. The purpose of the research is to increase public participation in using a contraceptive device fit through a cultural approach bobodoran as a media promotion of health. The research is quantitative, using quasi-experimental methods with the Pre and Post-test one group approaches. Retrieval of data by purposive sampling, and analysis of the data of different tests. The total sample in research 85 women are in their reproductive age. The result of this research by using Wilcoxon analysis or test showed that there was a rise in participation in a contraceptive device consistent with the objectives of the age of WUS, in addition, there were also increasing the knowledge and attitude related a contraceptive device before and after bobodoran performance culture. Health education with Bobodoran can increase the participation of family planning acceptors.